Gestão de crise de imagem em organizações educacionais - Ferreira, Ana Claudia Klein (Universidade do Vale do Rio dos Sinos, 2015)
In this study I searched for a look at the image crisis management in educational organizations about the practical reflection of management and organizational communication in the light of different knowledge. To answer "How educational organizations deal with risk situations of image crisis from the perspective of communication?", I did a scientific investigation through seven in-depth interviews with communication managers and also I did a focus group with seven private school principals of Porto Alegre, state of Rio Grande do Sul. From the obtained content, I did a triangulation with a theoretical framework involving areas of authors as administration, education and communication. Thus, it was possible to define analysis categories and achive the proposed objectives. Besides making evident how the educational organizations deal with situations of risk of image crisis from the perspective of communication, it was possible to analyze the role of communications area in schools in relation to the crisis management also understand what the risk factors of image crisis and protective factors perceived by managers in educational organizations. Among the most significant results is the observation that the directors are aware of the responsibility for their role in a crisis, however we can see a certain distance between communication area and school management. It was also evident lack of planning for a possible image crisis by organizations.
Keywords: Gestão de crise; Comunicação organizacional; Gestão educacional; Crisis management; Organizational communication; Educational management; ACCNPQ::Ciências Humanas::Educação